Correlation of Patient Generated-subjective Global Assessment with Serum C-reactive Protein Level in Stage I–IV Head-and-neck Cancer - Siregar, Anastasya; Chandra, Dian Novita; Rinaldi, Ikhwan (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: This study aims to identify the correlation between patient generated-subjective global assessment (PG-SGA) with serum C-reactive protein (CRP) to be used to predict inflammation and prevent cachexia in head-and-neck cancer patients. METHODS: This was a cross-sectional study using 51 patients with inclusion criteria of patients diagnosed with head-and-neck cancer irrespective of stage, age ≥18 years old, had not received treatments of radiotherapy, chemotherapy, and surgery. The statistical analysis performed was Kolmogorov–Smirnov normality test, bivariate analysis by Spearman test, and linear regression analysis. RESULTS: As many as 64.7% of the patients had PG-SGA score ≥9 (average PG-SGA score 11.7 ± 6.2). The CRP median value was 6.4 (0.4–170.4) mg/L. There was a statistically significant positive but weak correlation between PG-SGA score with serum CRP (r = 0.372 and p = 0.007) and a significant linear relationship (r2 = 0.201). CONCLUSIONS: Malnutrition risk assessment using PG-SGA showed a high prevalence of malnutrition risk in head-and-neck cancer patients. PG-SGA score is correlated with serum CRP level. Further studies are needed to confirm the result of this study.